Different hydraulic and photosynthetic responses to summer drought between newly sprouted and established Moso bamboo culms - Zhang, Xin; Tong, Chazi; Fang, Dongming; Mei, Tingting; Li, Yan (Frontiers in Plant Science, 2023)
The subtropical regions in China are prone to recurrent summer droughts induced by the Western Pacific Subtropical High-Pressure, which has induced the death of tens of millions of culms of Moso bamboo (Phyllostachys edulis (Carriere) J.Houzeau), a widely distributed giant bamboo with high economic and ecological values. In the future, the intensity and frequency of the summer drought are projected to increase in these areas due to global climate change, which may lead to significant age-specific mortality of Moso bamboo. So far, it is still unclear about the age-specific response mechanisms of hydraulic traits and carbon balance of Moso bamboo when it is suffering to an ongoing summer drought. This study aimed to investigate the hydraulic and photosynthetic responses of newly sprouted (1 year old) and established (2-5 years old) culms of Moso bamboo to summer drought, which was manipulated by throughfall reduction in Lin'an of Zhejiang. The results showed that both newly sprouted and established culms had a gradually weakening hydraulic conductivity and photosynthesis during the whole drought process. In the early stage of the manipulated drought, the established culms had more loss of hydraulic conductivity than the newly sprouted culms. However, the newly sprouted culms had significant more loss of hydraulic conductivity and lower photosynthetic rates and stomatal conductance in the middle and late stages of the manipulated drought. The results suggest that the newly sprouted culms were more susceptible to summer drought than established culms due to the combined effects of hydraulic damage and photosynthetic restriction, explaining why the newly sprouted culms have higher mortality than elder culms when subjected to extreme drought. These findings provided insights into the mechanisms of Moso bamboo's age-specific drought-induced mortality, which will help for the anti-drought management of bamboo.